Strategies to Enhance Early Implementation of Kangaroo Mother Care Guidelines in Health Facilities in Edo State, Nigeria - Esewe, Roselynd Ejakhianghe; Phetlhu, Rene Deliwe (International Journal of Nursing and Health Science, 2020)
This paper describes the second phase of the processes that culminated in the formulation of strategies to enhance early implementation of Kangaroo Mother Care (KMC) guidelines in health facilities in Edo state, Nigeria. A multi-method approach by the use of the health policy analysis triangle of Walt and Gilson in 1994 resulted in conclusion statements that were generated from an empirical study in phase 1. The knowledge, attitude, practice and socio-cultural barriers regarding KMC of 72 respondents: 55 operational health workers, 4 managers and 13 mothers of preterm infants was explored through a descriptive survey design. In phase II, a purposive method was applied to select 10 Delphi panelists. The Total Quality Management (TQM) philosophy served as a basis to develop a vision, mission, values, principles, assumptions, and strategic objectives. The quantitative Delphi approach was used with the aid of a self-administered questionnaire which was validated by pilot testing. Data obtained from the rounds of the Delphi technique were analyzed with SPPS (24) in non-parametric variables using measures of central tendencies. A 75% consensus was reached in round 3 as predetermined as the acceptable score in all domains by the Delphi panelists. Hence the strategies are authentic, applicable and reliable for use as verified by the experts. Based on the rigour involved in the development of the strategies, the operational health workers (OHWs) who may have difficulties initiating and providing kangaroo mother care will benefit immensely. Furthermore, the strategies have the potential to contribute to the knowledge base of nursing practice because, it may serve as a reference point for nurses in the Neonatal Intensive Care Unit (NICU), maternity units and Primary Health Care centers (PHCs) thus helping in the reduction of neonatal mortality.
Keywords: Kangaroo Mother Care; Health Facilities; Edo States; Strategy; Total Quality Management; Nigeria; ACE: Reproductive Health Innovation; CERHI; University of Benin; Reproductive Health